Complete genome arrangement revealed the emergence of a poultry origin superbug Citrobacter portucalensis strain NR-12. (September 2019) - Hasan, Md. Shazid; Sultana, Munawar; Hossain, M. Anwar
Highlights: Colistin-resistant Citrobacter spp. were retrieved from Bangladesh poultry farms. The complete genome of Citrobacter portucalensis strain NR-12 was analysed. Complete genome of C. portucalensis strain NR-12 revealed 13 antimicrobial resistance gene markers (AMRs). It conferred resistance to eight different antibiotics of six antimicrobial groups. It harbours class 1 integron (IntI1) gene cassette containing different AMRs ( dfr A12, aad A2, sul 1, mph (A)). Abstract: Objectives: Citrobacter spp. are part of normal human and animal intestinal flora. Citrobacter portucalensis ( C. portucalensis ) is closely related to Citrobacter freundii, which is an emerging opportunistic nosocomial pathogen. The aim of this study was to retrieve colistin-resistant Citrobacter spp. from poultry in Bangladesh. Methods: The C. portucalensis strain NR-12 was isolated from poultry droppings and subjected to antibiotic susceptibility testing. Complete genome analysis of NR-12 was performed followed by bioinformatics. It is believed that this is one of first reports of its kind of complete genome sequence of multidrug-resistant (MDR) C. portucalensis isolated from veterinary samples. Results: The C. portucalensis strain NR-12 showed resistance to polymyxin, sulfonamide, tetracycline, fluoroquinolone, and macrolide. Its complete genome revealed 13 acquired antimicrobial resistance gene markers (AMRs) conferring resistance to eight different antibiotic groups: dfr A12 (trimethoprim); sul 1 and sul 2 (sulfonamide); mph (A) (macrolide); tet (A) (tetracycline); qnr S1 and qnr B13 (fluoroquinolone); bla CMY-39 (extended-spectrum β-lactamase (ESBL)), bla TEM-176 (non-ESBL) and aad A2, aph (3′)-Ia, aph (3″)-Ib, aph (3′)-Ic, aph (3′)-Id, str A, str B) (aminoglycoside). The genome possessed a class 1 integron (IntI1) gene cassette harbouring four different antibiotic resistance genes ( dfr A12, aad A2, sul 1, mph (A)). The organisation of class 1 integron (IntI1) carrying MDR determinants in C. portucalensis strain NR-12 was also first reported here. Colistin-resistant genes such as mgr B, pho P, pho Q, pmr A, pmr B, ept B and arn B were also present within NR-12. Conclusion: C. portucalensis NR-12 was resistant to eight different antibiotics from six antimicrobial groups. To formulate a control strategy, it is important to understand this resistant mechanism.